1998
DOI: 10.1159/000021992
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein Profile and High-Density Lipoproteins: Subfractions Distribution in Centenarians

Abstract: In order to assess the role of HDL on longevity, we studied HDL subfraction distribution in centenarian women compared with a group of weight- and gender-matched healthy normolipidemic controls. We did not find any significant difference in the mean plasma lipid, apolipoprotein, and Lp(a) levels. On the contrary, in spite of similar HDL-cholesterol concentrations (1.32 ± 0.41 mmol/l in centenarians vs. 1.32 ± 0.25 mmol/l in controls, p = not significant), HDL2b and HDL3a levels were, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…Barbagallo et al examined HDL subfractions using polyacrylamide gradient gels in 16 female centenarians and 32 healthy normolipidemic postmenopausal women. They did not find any significant difference in lipid or apolipoprotein levels, however, the HDL2b level was increased, and the HDL3a level decreased in centenarians, compared to those in the controls (9). We have also demonstrated relatively higher levels of HDL2-C among 42 centenarians by ultracentrifugation (11).…”
Section: Hdl Cholesterol and Its Subpopulations In Centenariansmentioning
confidence: 50%
See 1 more Smart Citation
“…Barbagallo et al examined HDL subfractions using polyacrylamide gradient gels in 16 female centenarians and 32 healthy normolipidemic postmenopausal women. They did not find any significant difference in lipid or apolipoprotein levels, however, the HDL2b level was increased, and the HDL3a level decreased in centenarians, compared to those in the controls (9). We have also demonstrated relatively higher levels of HDL2-C among 42 centenarians by ultracentrifugation (11).…”
Section: Hdl Cholesterol and Its Subpopulations In Centenariansmentioning
confidence: 50%
“…However, results from centenarian studies have been conflicting. Some investigators have reported that centenarians showed a lipid profile similar to that of the middle-aged population (9), but others have demonstrated lower total and HDL cholesterol in centenarians (10,11). This discrepancy may be attributable to differences in sampling, and the nutritional and functional status of centenarians (this issue is also described in later paragraphs).…”
Section: Hdl Cholesterol and Its Subpopulations In Centenariansmentioning
confidence: 98%
“…66 Precedent data on the same sample demonstrated that, in spite of an independent and inverse association of total HDL-C levels with CAD in older women, no relation exists between any lipoprotein parameter and longevity in Italian centenarians. 67 Finally, healthy Italian centenarians had LDL-C significantly lower and HDL-C with an opposite trend compared to aged subjects, suggesting a less atherogenic plasma lipid and lipoprotein profile in centenarians than aged subjects. 68 Recently, low concentrations of TC and LDL-C, and a relative predominance of HDL2-C were found also in Japanese centenarians.…”
Section: Lipoproteins and Human Longevitymentioning
confidence: 88%
“…SAI was also significantly but moderately associated with interviewer-rated health, which provides support to its criterion validity. For biomarkers, SAI was related to greater high-density lipoprotein cholesterol which tends to be related to better cognitive capacity (Atzmon et al, 2002) and lower risks of coronary heart disease (Barbagallo et al, 1998). This pattern of associations provides support to the validity of SAI as an indicator of favorable health.…”
Section: Discussionmentioning
confidence: 64%